2023
DOI: 10.3390/s23249749
|View full text |Cite
|
Sign up to set email alerts
|

PosturePose: Optimized Posture Analysis for Semi-Supervised Monocular 3D Human Pose Estimation

Lawrence Amadi,
Gady Agam

Abstract: One motivation for studying semi-supervised techniques for human pose estimation is to compensate for the lack of variety in curated 3D human pose datasets by combining labeled 3D pose data with readily available unlabeled video data—effectively, leveraging the annotations of the former and the rich variety of the latter to train more robust pose estimators. In this paper, we propose a novel, fully differentiable posture consistency loss that is unaffected by camera orientation and improves monocular human pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…This adaptive function allows layers with more channels to engage in more inter-channel interactions. The specific adaptive function is described in Formula (10).…”
Section: Optimizing the Head Section Key Pointsmentioning
confidence: 99%
See 1 more Smart Citation
“…This adaptive function allows layers with more channels to engage in more inter-channel interactions. The specific adaptive function is described in Formula (10).…”
Section: Optimizing the Head Section Key Pointsmentioning
confidence: 99%
“…Through comparison with standard poses, the study demonstrated the algorithm's ability to accurately recognize various badminton action poses, with a recognition rate of up to 94%. Amadi et al [10] (2023) introduced a novel and fully differentiable pose consistency loss method. This method is unaffected by camera direction and has shown improvements in single-view human pose estimators trained using limited labeled 3D pose data.…”
Section: Introduction 21 Research Work By Relevant Scholarsmentioning
confidence: 99%